2016
DOI: 10.1186/s13054-016-1182-z
|View full text |Cite
|
Sign up to set email alerts
|

T cells from patients with Candida sepsis display a suppressive immunophenotype

Abstract: BackgroundDespite appropriate therapy, Candida bloodstream infections are associated with a mortality rate of approximately 40 %. In animal models, impaired immunity due to T cell exhaustion has been implicated in fungal sepsis mortality. The purpose of this study was to determine potential mechanisms of fungal-induced immunosuppression via immunophenotyping of circulating T lymphocytes from patients with microbiologically documented Candida bloodstream infections.MethodsPatients with blood cultures positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 35 publications
4
74
0
12
Order By: Relevance
“…Patients suffering from C. albicans fungal sepsis display elevated levels of PD-1 on CD8 + T cells, as well as increased expression of PD-L1 on both CD4 + and CD8 + T cells [114]. In this study, the control group was critically ill non-septic patients with no evidence of fungal infection, suggesting that septic infection with the fungal pathogen C. albicans was an important and specific determinant in activation of the PD signaling pathway.…”
Section: Immunoregulatory Signaling Pathwaysmentioning
confidence: 94%
“…Patients suffering from C. albicans fungal sepsis display elevated levels of PD-1 on CD8 + T cells, as well as increased expression of PD-L1 on both CD4 + and CD8 + T cells [114]. In this study, the control group was critically ill non-septic patients with no evidence of fungal infection, suggesting that septic infection with the fungal pathogen C. albicans was an important and specific determinant in activation of the PD signaling pathway.…”
Section: Immunoregulatory Signaling Pathwaysmentioning
confidence: 94%
“…Given the fundamental role of Th17 in eradication of pathologic fungal infections, reduced Th17 cytokine production in sepsis is probably responsible for the increased susceptibility to fungal infections frequently observed in critically ill populations . Circulating CD4 + and CD8 + cells from patients with candidemia display an immune phenotype consistent with immune suppression, T‐cell exhaustion, and downregulation of positive co‐stimulatory molecules . Moreover, IL‐7 treatment has been demonstrated to increase Th17 cell responsiveness and reduce mortality from secondary fungal infections, making IL‐17 a potential therapeutic agent .…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…190 Circulating CD4 + and CD8 + cells from patients with candidemia display an immune phenotype consistent with immune suppression, T-cell exhaustion, and downregulation of positive co-stimulatory molecules. 191 Moreover, IL-7 treatment has been demonstrated to increase Th17 cell responsiveness and reduce mortality from secondary fungal infections, making IL-17 a potential therapeutic agent. 177 These findings may help explain why patients with fungal sepsis have a high mortality despite appropriate antifungal therapy.…”
Section: T H Cell Subpopulationsmentioning
confidence: 99%
“…T cell proliferation is also impaired during sepsis [22, 23, 51, 71]. Recent reports show that PD-1 expression is significantly increased on peripheral blood CD4+ and CD8+ T cells during Candida bloodstream infection associated with CD8+ T cell activation (increased CD69 expression), a decrease in co-stimulatory CD28 expression and IL-7R expression [72]. Another prospective clinical study showed that as sepsis progressed, T lymphocytes in blood show increased expression of TIM-3, LAG-3, CTLA-4 and decreased IL-7R expression and IFN-γ secretion upon ex vivo simulation, along with an increased PD-L1 expression on dendritic cells [56].…”
Section: Sepsis-induced T Cell Dysfunctionmentioning
confidence: 99%